2001
DOI: 10.1023/a:1005672631019
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Diabetes management by insulin administration is based on medical experts' experience, intuition, and expertise. As there is very little information in medical literature concerning practical aspects of this issue, medical experts adopt their own rules for insulin regimen specification and dose adjustment. This paper investigates the application of a neural network approach for the development of a prototype system for knowledge classification in this domain. The system will further facilitate decision making … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…NNs have the capability to train and process complex functions in many applications including identification, pattern recognition, speech processing, classification, and control systems [ 21 ]. NNs are implemented for diabetic diagnosis [ 22 ], for analyzing blood glucose range as a primary indicator of the diabetic condition, in addition to diabetic management and associated insulin administration [ 22 ]. NNs reveal their utility and efficiency in solving problems that require prediction, clinical diagnosis, pattern recognition, and/or image analysis.…”
Section: The Proposed Methods For Non-invasive Glucose Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…NNs have the capability to train and process complex functions in many applications including identification, pattern recognition, speech processing, classification, and control systems [ 21 ]. NNs are implemented for diabetic diagnosis [ 22 ], for analyzing blood glucose range as a primary indicator of the diabetic condition, in addition to diabetic management and associated insulin administration [ 22 ]. NNs reveal their utility and efficiency in solving problems that require prediction, clinical diagnosis, pattern recognition, and/or image analysis.…”
Section: The Proposed Methods For Non-invasive Glucose Extractionmentioning
confidence: 99%
“…A system is designed in [ 22 ] to provide testing of diabetic abnormalities, where NNs are used in the early stages of diabetic diagnosis. Input parameters to the NN classifier include the number of times a patient has been pregnant, their plasma glucose concentration, blood pressure, body mass index, and insulin production level [ 22 ]. Results of the research revealed the NNs capable of learning patterns corresponding to diabetic symptoms of an individual, achieving an accuracy of 98% [ 22 ].…”
Section: The Proposed Methods For Non-invasive Glucose Extractionmentioning
confidence: 99%
“…Gogou et al . [ 11 ] stated that using a FPN to model fuzzy rule based reasoning provides a couple of advantages:…”
Section: Defining Fuzzy Variable and Fuzzy Rulesmentioning
confidence: 99%
“…Gogou et al . [ 11 ] used the neural network for an INS administration system to manage the diabetics. Ward and Martin[ 19 ] used a fuzzy inference system to propose a glucose regulation model.…”
Section: Related Workmentioning
confidence: 99%
“…Concepts developed in the DIADOQ and the ByMedCard system were used to implement the DCDS in the DIABCARD Core System (Fig. 4) [12], the electronic patient record for all 8 sites. First evaluation of the system has been performed leading to an optimised user and functional adaptation.…”
Section: Review Papermentioning
confidence: 99%